2018
DOI: 10.3390/w10111567
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Efficacy and Disinfection by-Product Formation of a Coagulant/Disinfectant Tablet for Point-of-Use Water Treatment

Abstract: Coagulant/disinfection products (CDPs) are a point-of-use (POU) water treatment technique that can improve microbial quality, reduce turbidity, and produce a free chlorine residual (FCR), serving as a potentially effective option for decentralized water treatment in a variety of contexts, including humanitarian emergencies. A novel CDP with a sodium dichloroisocyanurate-based disinfectant was evaluated with regard to its laboratory water treatment efficacy and generation of disinfection byproducts (DBPs). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interestingly, Lantange et al [7,8] in their study of TTHM production in household chlorination programs in Kenya and Tanzania observed that chloroform was the dominant THM species in the samples they analyzed, contributing on average 78% and 83% of TTHM content across multiple water types in either country, respectively. Similarly, Légaré-Julien et al [34] also found the speciation of TTHMs to be primarily chloroform when natural surface waters were chlorinated. This reinforces the assumption that the DBP/THM reading produced by the Hach THM Plus method can meaningfully be compared to the WHO chloroform guideline as the majority species is indeed likely to be chloroform.…”
Section: Dbp/thm Guidelinesmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, Lantange et al [7,8] in their study of TTHM production in household chlorination programs in Kenya and Tanzania observed that chloroform was the dominant THM species in the samples they analyzed, contributing on average 78% and 83% of TTHM content across multiple water types in either country, respectively. Similarly, Légaré-Julien et al [34] also found the speciation of TTHMs to be primarily chloroform when natural surface waters were chlorinated. This reinforces the assumption that the DBP/THM reading produced by the Hach THM Plus method can meaningfully be compared to the WHO chloroform guideline as the majority species is indeed likely to be chloroform.…”
Section: Dbp/thm Guidelinesmentioning
confidence: 86%
“…Similarly, Nhongo et al [40] found THMs to generally be within WHO guideline limits in their investigation of DBP levels in the piped water supply system of Harare, Zimbabwe. Légaré-Julien et al [34] found THM levels in the range of 50 ppb when natural surface waters from Quebec, Canada were treated using a point-of-use coagulant-disinfectant product that included NaDCC as the disinfecting agent. On the other hand, Werner et al [41] found levels of chloroform and TTHMs approaching and even exceeding the 300 ppb WHO guideline at 24 h when point-of-use chlorine dioxide tablets were used to treat natural surface waters in the Northern British Isles.…”
Section: Discussionmentioning
confidence: 99%
“…This applies even if laboratory assessments are intended to simulate challenging conditions, for example the use of a high-turbidity, high-organic-content test water 25,29,39 . Laboratory assessments can be effectively employed to identify water quality-or treatmentrelated limitations of products and screen performance between several design conditions 40,41 , options or products 42,43 .…”
Section: Pouwt Performance In the Laboratory And Field Methodsmentioning
confidence: 99%